Composite food freshness indicating film and preparation method thereof

The pre-coated film is covered on the anthocyanin food freshness indicating film through thermal lamination technology to form a purple sweet potato/plastic composite film, which solves the problem of insufficient mechanical properties and moisture resistance of the existing film and realizes the application in high-humidity environments. Stability indication function.

CN119329150APending Publication Date: 2025-01-21YANGZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411126677.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-16
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The freshness indicator film of existing anthocyanins foods has poor mechanical properties and moisture resistance, making it difficult to maintain stability in a high-humidity food packaging environment, and hydrophilic substances are prone to dissolve and lose their indicator function.

Method used

The commercial pre-coated film is covered on the anthocyanin food freshness indicator film through thermal lamination technology to form a purple sweet potato/plastic composite film to improve mechanical properties and moisture resistance.

Benefits of technology

The mechanical strength, moisture resistance and stability of the food freshness indicating film are significantly improved, and the indicating function is maintained in a high-humidity environment. It is easy to operate and low in cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119329150A_ABST
    Figure CN119329150A_ABST
Patent Text Reader

Abstract

The invention discloses a composite food freshness indicating film and a preparation method thereof, the film comprises an anthocyanin food freshness indicating film and a commercialized pre-coating film, and the commercialized pre-coating film is utilized to perform thermal mounting and film covering on the anthocyanin food freshness indicating film through a thermal mounting technology to obtain the composite film. The anthocyanin food freshness indicating film is combined with plastic through a hot mounting technology, so that the original color, color changing performance and food freshness indicating function of a purple sweet potato film are well reserved, and good mechanical performance, integrity and stability can be kept in a high-humidity food packaging environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a food freshness indicator film, in particular to a composite food freshness indicator film and a preparation method thereof. Background Art

[0002] The combination of natural pigments and biodegradable biopolymers can be used to prepare food freshness indicator films, which are used to sense changes in the pH of the food packaging environment and effectively indicate the freshness of the food through changes in the color of the film. Among many natural pigments, anthocyanins have excellent pH-responsive color-changing ability and are suitable for the preparation of food freshness indicator films. However, the mechanical properties and moisture resistance of food freshness indicator films prepared using anthocyanins and biopolymers are poor, making it difficult to meet actual food packaging needs. Especially in a high-humidity food packaging environment, the film will absorb moisture and swell, reducing its mechanical strength; at the same time, the hydrophilic anthocyanins will dissolve from the film, causing the film to lose its function of indicating the freshness of food.

[0003] A large number of studies have shown that the mechanical properties and moisture resistance of anthocyanin food freshness indicator membranes can be partially improved through electrospinning technology, multilayer membrane technology, and the addition of hydrophobic substances to the membrane. However, the existing technologies have the following defects: the electrospinning technology has a complex process, expensive equipment, low yield, and low mechanical strength of the prepared membrane; the multilayer membrane technology has a long membrane preparation cycle and high cost; and the hydrophobic substances added to the membrane have poor compatibility with other hydrophilic membrane components and cannot significantly improve the mechanical properties of the membrane.

[0004] The latest research has found that compounding anthocyanin food freshness indicator film with commercial plastic film can significantly improve the mechanical properties and moisture resistance of the food freshness indicator film. The existing methods for preparing composite films mainly include cast film method and coating method. Among them, the cast film method is to cast a biopolymer solution containing anthocyanins on the surface of a plastic film and then dry it to obtain a composite film. However, the uniformity of the composite film prepared by this method is poor, and the bonding tightness between the anthocyanin film and the plastic film is low, and the two are easy to separate. The coating method is to apply a biopolymer solution containing anthocyanins on the surface of a plastic film. The composite film prepared by this method also has the defect of uneven distribution of anthocyanins. Summary of the invention

[0005] Purpose of the invention: The first purpose of the present invention is to provide a composite food freshness indicator film with improved mechanical properties and moisture resistance; the second purpose of the present invention is to provide a method for preparing the composite food freshness indicator film.

[0006] Technical solution: The composite food freshness indicator film of the present invention comprises an anthocyanin food freshness indicator film and a commercial pre-coated film. The anthocyanin food freshness indicator film is thermally laminated with the commercial pre-coated film by thermal lamination technology to obtain a composite film.

[0007] The anthocyanin food freshness indicator film is a purple sweet potato film.

[0008] Preferably, the commercial pre-coating film is a PET film or a BOPP film. Both the PET pre-coating film and the BOPP pre-coating film have excellent mechanical strength, moisture barrier properties and transparency.

[0009] The preparation method of the composite food freshness indicator film of the present invention comprises the following steps: performing a heat-laminating film coating process on a heat-laminating machine assembled with a commercial pre-coated film to obtain a composite film;

[0010] The anthocyanin food freshness indicator film is a purple sweet potato film, and the preparation method comprises the following steps:

[0011] (1) The purple sweet potato is sterilized by high pressure steam and then homogenized to obtain purple sweet potato juice;

[0012] (2) adding a plasticizer to the purple sweet potato juice obtained in step (1) to obtain a mixed solution of purple sweet potato juice and the plasticizer;

[0013] (3) pouring the mixed solution of purple sweet potato juice and plasticizer obtained in step (2) into a mold and drying it to obtain a purple sweet potato film.

[0014] Preferably, when the pre-coating film is a PET pre-coating film, the heat mounting treatment temperature is 110-160°C. Preferably, when the pre-coating film is a BOPP pre-coating film, the heat mounting treatment temperature is 80-130°C. If the laminating temperature is too low, the adhesive layer of the pre-coating film is difficult to melt and cannot be tightly bonded to the purple sweet potato film; if the laminating temperature is too high, the anthocyanin in the purple sweet potato film will be degraded, and the pre-coating film will also shrink, curl and partially bubble.

[0015] Preferably, the speed of the heat mounting process is 0.5-2 m / min.

[0016] Preferably, in step (1), the high-pressure steam sterilization treatment is to place the purple sweet potato in a sterilizing pot and maintain it at 115-121° C. for 30-40 minutes at 103.4 kPa.

[0017] Preferably, in step (1), the homogenization is performed by adding the purple sweet potato sterilized by high-pressure steam into hot water and homogenizing the purple sweet potato, the temperature of the hot water is 80-100° C., and the material-liquid ratio of the purple sweet potato to the hot water is 1:15-1:25 g / mL.

[0018] Preferably, in step (2), the plasticizer is polyethylene glycol, and the added amount of polyethylene glycol is 10% to 30% of the weight of the purple sweet potato.

[0019] Preferably, in step (3), the size of the mold is 10-20 cm×10-20 cm; the drying temperature is 30-50° C., and the drying time is 16-48 h.

[0020] Invention mechanism: The present invention first prepares the purple sweet potato film by the traditional casting method, and then covers the single surface of the purple sweet potato film with the commercial pre-coating film by the hot laminating technology to prepare the purple sweet potato / plastic composite film. During the high-temperature hot laminating treatment, the adhesive in the commercial pre-coating film will melt, and the purple sweet potato film and the commercial pre-coating film can be tightly bonded together under the pressure of the hot laminating machine rubber roller; the commercial pre-coating film is used to enhance the mechanical properties and moisture resistance of the purple sweet potato film. In addition, the commercial pre-coating film has high transparency and will not affect the original color, color change performance and food freshness indication function of the purple sweet potato film.

[0021] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) The anthocyanin food freshness indicator film is combined with plastic by heat-mounting technology, which well preserves the original color, color-changing performance and food freshness indication function of the purple sweet potato film, and can maintain good mechanical properties, integrity and stability in a high-humidity food packaging environment; (2) The commercial pre-coated film is covered on a single surface of the purple sweet potato film by heat-mounting technology, which improves the mechanical strength and moisture resistance of the purple sweet potato film; (3) The preparation of the purple sweet potato / plastic composite film by heat-mounting technology has the advantages of simple operation, short time, low cost and uniform film formation. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The scanning electron microscope images of Example 1, Example 2, Example 3, Comparative Example 1 and Comparative Example 2 of the present invention are shown;

[0023] Figure 2 The infrared spectra of Example 1, Example 2, Example 3, Comparative Example 1 and Comparative Example 2 of the present invention are shown;

[0024] Figure 3 The X-ray diffraction patterns of Example 1, Example 2, Example 3, Comparative Example 1 and Comparative Example 2 of the present invention are shown in FIG.

[0025] Figure 4 The figures are the mechanical properties of Example 1, Example 2, Example 3, Comparative Example 1 and Comparative Example 2 of the present invention; wherein 4A is the tensile strength (TS) figure, and 4B is the elongation at break (EAB) figure;

[0026] Figure 5 5A is a thermogravimetric analysis diagram of Example 1, Example 2, Example 3, Comparative Example 1 and Comparative Example 2 of the present invention; wherein 5A is a thermogravimetric curve (TGA), and 5B is a thermogravimetric differential curve (DTG);

[0027] Figure 6It is a water vapor transmission rate (WVP) diagram of Example 1, Example 2, Example 3, Comparative Example 1 and Comparative Example 2 of the present invention;

[0028] Figure 7 The water contact angle (WCA) diagrams of Example 1, Example 2, Example 3, Comparative Example 1 and Comparative Example 2 of the present invention are shown;

[0029] Figure 8 The water adsorption isotherms of Example 1, Example 2, Example 3 and Comparative Example 1 of the present invention are shown;

[0030] Figures 9-11 This is a stability test diagram of Example 1, Example 2, Example 3 and Comparative Example 1 of the present invention in water; wherein, Fig. 9 is the swelling diagram of the membrane sample in water, Fig.10 is the DPPH free radical scavenging activity diagram of the membrane extract. Fig.11 is the UV-visible spectrum of the membrane leachate;

[0031] Fig.12 A is a photo of Example 1, Example 2, Example 3 and Comparative Example 1 of the present invention; Fig.12 B is a graph of UV-visible light transmittance of Example 1, Example 2, Example 3 and Comparative Example 1 of the present invention;

[0032] Fig.13 13A is a color change performance diagram of the membrane sample in a pH 3-12 buffer solution, and 13B is a color change performance diagram of the membrane sample in an ammonia atmosphere;

[0033] Fig.14 14A is a graph showing the color change of the film sample during storage, and 14B is a graph showing the ΔE value change of the color change of the film sample during storage;

[0034] Fig.15 These are performance diagrams indicating the freshness of shrimps in Example 1, Example 2, Example 3 and Comparative Example 1 of the present invention; wherein 15A is a diagram showing the color change of the film, and 15B is a diagram showing the pH value and total volatile basic nitrogen (TVB-N) value change of the shrimps during storage. DETAILED DESCRIPTION

[0035] The technical solution of the present invention is further described below in conjunction with embodiments.

[0036] Example 1

[0037] The composite food freshness indicator film of the present invention comprises the following steps:

[0038] (1) Wash fresh purple sweet potatoes, place them in an autoclave, and maintain them at 121° C. for 30 min at 103.4 kPa; weigh 8 g of sterilized purple sweet potatoes, add them into 160 mL of 100° C. hot water, and use a high-speed disperser to homogenize them at a speed of 10,000 rpm for 3 min to obtain purple sweet potato juice;

[0039] (2) adding 2.4 g of polyethylene glycol to the purple sweet potato juice to obtain a purple sweet potato juice / polyethylene glycol mixed solution;

[0040] (3) pouring the purple sweet potato juice / polyethylene glycol mixed solution into a mold (20 cm×20 cm) and drying at 40° C. for 36 h to obtain a purple sweet potato film;

[0041] (4) The purple sweet potato film and the commercial PET pre-coated film were subjected to a heat lamination process on a heat laminating machine, with the heat lamination temperature controlled at 120° C. and the heat lamination speed controlled at 2 m / min to obtain a purple sweet potato / PET composite film 1, which was named PSP / PET-120.

[0042] Example 2

[0043] The composite food freshness indicator film of the present invention comprises the following steps:

[0044] The hot mounting temperature in step (4) of Example 1 was adjusted to 140° C., and the other preparation conditions remained unchanged to obtain a purple sweet potato / PET composite film 2, which was named PSP / PET-140.

[0045] Example 3

[0046] The composite food freshness indicator film of the present invention comprises the following steps:

[0047] The hot mounting temperature in step (4) of Example 1 was adjusted to 160° C., and the other preparation conditions remained unchanged to obtain a purple sweet potato / PET composite film 3, which was named PSP / PET-160.

[0048] Comparative Example 1

[0049] A purple sweet potato film that has not been subjected to heat-mounting lamination treatment, the preparation method comprising the following steps:

[0050] The purple sweet potato film obtained in steps (1) to (3) of Example 1 is not subjected to the heat-mounting and laminating treatment of step (4) and is named PSP.

[0051] Comparative Example 2

[0052] A commercial PET pre-coated film without any treatment is named PET.

[0053] 1. Structural Characterization of Membranes

[0054] Scanning electron microscopy, infrared spectroscopy and X-ray diffraction tests were performed on Example 1, Example 2, Example 3, Comparative Example 1 and Comparative Example 2.

[0055] (1) The surface and cross-sectional microstructure of the membrane samples were observed using a scanning electron microscope. Figure 1 shown.

[0056] Depend on Figure 1 It can be seen that the surface of the PSP film is rough with obvious protrusions, while the PET film has a smooth surface. Compared with the PSP film, the surface of the PSP side of the PSP / PET-120, PSP / PET-140 and PSP / PET-160 films gradually becomes flat, indicating that the molecular arrangement of the PSP layer tends to be orderly as the heat mounting temperature increases. The cross-sectional view of the film shows that the PSP film has a greater thickness than the PET film, but there are a small number of micropores in the film cross-section of the PSP film, and the structure is relatively loose. In contrast, the cross-section of the PET film is denser. It is worth noting that there is no separation between the PSP layer and the PET layer in the PSP / PET-120, PSP / PET-140 and PSP / PET-160 films, indicating that the PET film and the PSP film are tightly bonded after the heat mounting process. Among the three PSP / PET composite films, the cross-sectional holes of the PSP layer in the PSP / PET-160 film are more, which may be caused by the rapid evaporation of water in the PSP layer due to the excessively high heat mounting temperature. The above results show that the heat mounting treatment temperature has a certain influence on the surface and internal morphology of the PSP / PET composite film.

[0057] (2) Using the attenuated total reflection mode of Fourier transform infrared spectrometer, the film samples were recorded at 400-4000 cm -1 Infrared spectrum in the range, the results are as follows Figure 2 shown.

[0058] Depend on Figure 2 It can be seen that the infrared spectra of PSP film and PET film are quite different. The infrared spectra of PSP film are at 3280 cm -1 (OH stretching vibration), 2924cm -1 (CH stretching vibration), 1605cm -1 (C=C stretching) and 1148-1018cm -1 (CO stretching vibration) shows a characteristic peak; while the PET film has a peak at 3426cm -1 (OH stretching vibration), 1714cm -1 (C=O stretching vibration), 1242cm -1 (C–O–C stretching vibration) and 1098 cm -1(H vibration on benzene ring-δ(CH)) presents a characteristic peak. The two sides of PSP / PET-120, PSP / PET-140 and PSP / PET-160 films have different infrared spectra, where the PSP side of these films has the same infrared spectrum as the PSP film, and the PET side of these films has an infrared spectrum similar to the PET film. It is worth noting that compared with the PET film, the OH stretching vibration on the PET side of the PSP / PET-120, PSP / PET-140 and PSP / PET-160 films is weakened, which may be due to the melting of the self-adhesive in the PET film during the hot lamination process and its tight adhesion to the PSP film. There is no significant difference in the infrared spectra of the three PSP / PET composite films, indicating that the hot lamination treatment temperature has little effect on the structure of the components of the PSP / PET composite film.

[0059] (3) Use a polycrystalline X-ray diffractometer to scan the X-ray diffraction pattern of the film sample at 5-65°, with a scanning speed of 2° / min. The test results are as follows: Figure 3 shown.

[0060] Depend on Figure 3 It can be seen that the PSP film has a broad peak near 20°, showing an amorphous state; while the PET film has a sharp crystalline peak at 26.2°. PSP / PET-120, PSP / PET-140 and PSP / PET-160 films have a broad peak of PSP film and a crystalline peak of PET film. Compared with the PET film, the intensity of the PET characteristic crystalline peak of PSP / PET-120, PSP / PET-140 and PSP / PET-160 films is reduced, which may be because the PSP layer weakens the penetration ability of X-rays.

[0061] 2. Test of the physical and chemical properties of the membrane

[0062] 1. The mechanical properties and thermogravimetric properties of Example 1, Example 2, Example 3, Comparative Example 1 and Comparative Example 2 were tested, and the test results are as follows:

[0063] (1) Use a universal tensile testing machine to measure the mechanical properties of the membrane sample. The test results are as follows: Figure 4 shown.

[0064] Figure 4A shows that the mechanical strength of the PSP film is relatively low (TS=7.66MPa), while the PET film has a relatively high mechanical strength (TS=31.60MPa). It is worth noting that the mechanical strength of the PSP film is significantly improved by compounding the PSP film with the PET film through heat lamination. Compared with the PSP film, the TS values ​​of the PSP / PET-120, PSP / PET-140 and PSP / PET-160 films increased by 198%, 185% and 183%, respectively. Among the three PSP / PET composite films, the TS value of the PSP / PET-120 film is higher. This may be because the excessively high heat lamination temperature will cause excessive evaporation of moisture in the PSP layer, forming holes and thus reducing the mechanical strength. Figure 4 B shows that both PSP film and PET film have good ductility, with EAB values ​​of 49.09% and 38.06%, respectively. The EAB values ​​of PSP / PET-120, PSP / PET-140 and PSP / PET-160 films are between those of PSP film and PET film. The EAB values ​​of PSP / PET-120, PSP / PET-140 and PSP / PET-160 films gradually increase, which may be because as the hot lamination temperature increases, the internal pores of the PSP layer in the PSP / PET composite film increase and the gaps between molecules increase. The above results show that hot lamination treatment can significantly enhance the mechanical strength of the PSP film while maintaining the good ductility of the PSP film.

[0065] (2) Under the condition of nitrogen flow rate of 20 mL / min, the thermogravimetric properties of the membrane sample were measured using a thermogravimetric analyzer, and the TGA and DTG curves of the membrane sample were recorded in the temperature range of 50 to 650 °C. The test results are as follows: Figure 5 shown.

[0066] Depend on Figure 5 It can be seen that the PSP film has three thermal decomposition stages: 50-160℃, 160-402℃, and 402-650℃, which correspond to the evaporation of water, the degradation of film components, and the formation of biochar, respectively. The fastest thermal degradation temperature of the PSP film is 208℃. In contrast, the PET film has higher thermal stability and only thermally degrades after 400℃, with the fastest thermal degradation temperature being 438℃. Compared with the PSP film, the thermal degradation process of the PSP / PET-120, PSP / PET-140, and PSP / PET-160 films is relatively slow; their fastest thermal degradation temperatures are 210-211℃, slightly higher than that of the PSP film. The results show that the thermal lamination treatment enhances the thermal stability of the PSP film. With the increase of the thermal lamination temperature, the thermal stability of the three PSP / PET composite films gradually decreases, which is due to the negative impact of the excessively high thermal lamination temperature on the compactness of the PSP layer of the PSP / PET composite film.

[0067] 3. The WVP, WCA, water adsorption isotherm and stability in water of Example 1, Example 2, Example 3 and Comparative Example 1 were tested, and the test results are as follows:

[0068] (1) The WVP of the membrane sample was determined using the gravimetric method. The test results are as follows: Figure 6 shown.

[0069] Depend on Figure 6 It can be seen that the WVP value of PSP film is higher and the water vapor barrier capacity is poor; while the PET film can almost completely block the permeation of water vapor and has extremely excellent water vapor barrier capacity. Compared with the PSP film, the WVP of PSP / PET-120, PSP / PET-140 and PSP / PET-160 films decreased by 94.4%, 94.2% and 94.0%, respectively, which is due to the higher water vapor barrier capacity of the PET layer. The results show that heat lamination can significantly improve the water vapor barrier properties of PSP film.

[0070] (2) The WCA and delayed stability of the film samples were measured using a water contact angle meter. The test results are as follows: Figure 7 shown.

[0071] Depend on Figure 7 It can be seen that the initial WCA of the smooth surface of the PSP film (the surface bonded to the PET film) was only 64.7°, which decreased to 48.4° after 120s; while the initial WCA of the rough surface of the PSP film was 103.0°, which decreased to 66.0° after 120s, indicating that the PSP film is a hydrophilic film; the initial WCA of the PET film was 86.8°, which decreased to 80.7° after 120s, indicating that it is a hydrophobic film. The initial WCA of the PET side of the PSP / PET-120, PSP / PET-140 and PSP / PET-160 films were 83.4°, 84.4° and 83.8°, respectively, and they were all stably maintained at around 80° within 120s, showing excellent delayed hydrophobic stability. The initial WCA of the PSP side of PSP / PET-120, PSP / PET-140 and PSP / PET-160 films were 100.5°, 96.1° and 93.6°, respectively, which were slightly lower than the rough surface of the PSP film. This may be because the mechanical extrusion of the film during the hot lamination process reduced the roughness of the film surface. After 120s, the WCA of the PSP side of PSP / PET-120, PSP / PET-140 and PSP / PET-160 films decreased to 66.3°, 68.3° and 67.5°, respectively. The results show that hot lamination can partially improve the hydrophobicity of PSP film. At the same time, the hot lamination temperature has no significant effect on the surface hydrophobicity of PSP / PET composite film.

[0072] (3) The test results of the adsorption isotherm of the membrane sample are as follows Figure 8 shown.

[0073] Depend on Figure 8 It can be seen that the adsorption isotherms of PSP film and PSP / PET-120, PSP / PET-140 and PSP / PET-160 films show similar trends, showing the characteristics of type II isotherms. When the relative humidity is less than 60%, there is no significant difference in the adsorption isotherms of PSP film and PSP / PET-120, PSP / PET-140 and PSP / PET-160 films, but when the relative humidity is greater than 60%, the moisture content in PSP / PET-120, PSP / PET-140 and PSP / PET-160 films is significantly lower than that in PSP film, indicating that hot mounting treatment can significantly improve the moisture resistance of PSP film in high humidity environment. In addition, the hot mounting treatment temperature has no significant effect on the moisture resistance of PSP / PET composite film.

[0074] (4) The membrane sample (1 cm × 1 cm) was immersed in a container containing 3 mL of distilled water. The swelling of the membrane was recorded every 2 min. The membrane extract was collected for determination of DPPH free radical scavenging ability and UV-visible spectrum. The test results are shown in Figures 9-11 shown.

[0075] Depend on Fig. 9 It can be seen that the PSP film rapidly absorbed water and swelled within 2 minutes. As time went on, the film gradually expanded. At 10 minutes, the film was almost dissolved and dispersed in water. In contrast, the PSP / PET-120, PSP / PET-140 and PSP / PET-160 films did not swell significantly in water and remained intact at 10 minutes. The results show that heat mounting can significantly enhance the stability of PSP film in water.

[0076] Depend on Fig.10 It can be seen that as the immersion time of the membrane in water increases, the DPPH scavenging activity of the membrane extracts shows a gradual upward trend. Compared with the PSP membrane extracts, the DPPH scavenging activity of the PSP / PET-120, PSP / PET-140 and PSP / PET-160 membrane extracts has a slower upward trend, indicating that the heat mounting treatment can effectively delay the release of anthocyanins in the PSP membrane. It is worth noting that the DPPH scavenging activity of the PSP / PET-160 membrane extract is slightly higher than that of the PSP / PET-120 and PSP / PET-140 membrane extracts, which may be because the PSP layer of the PSP / PET-160 membrane has more pores, which promotes the release of anthocyanins.

[0077] Depend on Fig.11It can be seen that compared with the PSP film, the absorbance values ​​of the characteristic peaks of the UV-visible spectra of the PSP / PET-120, PSP / PET-140 and PSP / PET-160 film extracts are significantly lower and increase more slowly, further proving that the heat mounting treatment can effectively delay the release of anthocyanins from the PSP film. In addition, the release rate of anthocyanins from the PSP / PET-160 film is significantly higher than that of the PSP / PET-120 and PSP / PET-140 films.

[0078] 4. Film color-related properties test

[0079] The appearance, UV-visible light transmittance, color changing ability and storage stability of Example 1, Example 2, Example 3 and Comparative Example 1 were tested, and the test results are as follows:

[0080] (1) Cover the film sample on a white paper with English letters and take a photo. Use a UV-visible spectrophotometer to measure the transmittance of the film sample in the range of 200 to 800 nm. The test results are as follows: Fig.12 shown.

[0081] Depend on Fig.12 It was found that PSP, PSP / PET-120, PSP / PET-140 and PSP / PET-160 films were all purple, and all films had good transparency and flexibility. In addition, the transmittance of PSP / PET-120, PSP / PET-140 and PSP / PET-160 films was not significantly different from that of PSP film. The results showed that the heat lamination treatment did not significantly change the original color and transparency of PSP film.

[0082] (2) After soaking the membrane sample in a buffer solution with a pH of 3 to 12 for 60 seconds, take a photo and record the color change of the membrane sample. The test results are as follows: Fig.13 As shown in A.

[0083] Depend on Fig.13 A shows that PSP, PSP / PET-120, PSP / PET-140 and PSP / PET-160 films show a relatively consistent color change trend (red→purple→purple→green) in different pH buffers. The results show that the heat mounting treatment does not affect the excellent pH-responsive color change characteristics of the film.

[0084] (3) The membrane sample was exposed to a volatile ammonia atmosphere with a concentration of 50 mM for 120 min, and the color change of the membrane sample was recorded by taking a photo. The test results are as follows: Fig.13 As shown in B.

[0085] Depend on Fig.13B shows that the PSP, PSP / PET-120, PSP / PET-140 and PSP / PET-160 films show relatively consistent and obvious color changes (purple→gray-green→green) in the atmosphere of volatile ammonia. The results show that the thermal lamination treatment does not affect the excellent ammonia-responsive color change characteristics of the film in the atmosphere of ammonia.

[0086] (4) The film samples were stored at 20°C for 36 days. Every 4 days, photos were taken to record the color changes of the film samples, and the ΔE value changes of the films were calculated. The test results are shown in Fig.14 shown.

[0087] Depend on Fig.14 It can be seen that after storage at 20°C for 36 days, PSP, PSP / PET-120, PSP / PET-140 and PSP / PET-160 films can all maintain their original purple color. Among them, the ΔE value of the PSP film changes slightly more than 5. Compared with the PSP film, the ΔE values ​​of the PSP / PET-120 and PSP / PET-140 films change less, indicating that the PSP / PET-120 and PSP / PET-140 films have higher storage stability. It is worth noting that the ΔE value change of the PSP / PET-160 film is slightly higher than that of the PSP / PET-120 and PSP / PET-140 films. This may be because the excessively high hot-mounting temperature makes the anthocyanins in the PSP / PET-160 film unstable and partially degrades, affecting the stability of the film during storage. The above results show that the hot-mounting treatment temperature of 120°C and 140°C will not have a negative impact on the storage stability of the PSP film.

[0088] 5. Application of membrane

[0089] Example 1, Example 2, Example 3 and Comparative Example 1 were used for shrimp freshness indication, and the test results were as follows:

[0090] The film sample was fixed to the inside of the top cover of a transparent fresh-keeping box with tape, and 170 g of fresh shrimp was placed in the fresh-keeping box, the top cover was closed, and the shrimp was stored at 4°C for 5 days. Every 24 hours, photos were taken to record the color changes of the film sample and the pH value and TVB-N value of the shrimp were measured. The results are as follows: Fig.15 shown.

[0091] Depend on Fig.15A: It can be seen that PSP, PSP / PET-120, PSP / PET-140 and PSP / PET-160 films all show obvious color changes during the storage of shrimp, which can be perceived by consumers with the naked eye. It is worth noting that in a high-humidity food packaging environment, the PSP film swells severely and separates from the fresh-keeping box lid on the second day due to its strong hygroscopicity. At the same time, a large number of bubbles are generated between the PSP film and the fresh-keeping box lid, which seriously affects consumers' observation of the film. However, due to their good moisture resistance, the PSP / PET-120, PSP / PET-140 and PSP / PET-160 films all remain stable within the fifth day and do not separate from the fresh-keeping box lid, which will not affect consumers' observation of the film.

[0092] Depend on Fig.15 B It can be seen that during storage in a 4°C refrigerator, the pH value and TVB-N value of the shrimp continued to increase. On the third day of storage, the TVB-N value of the shrimp had exceeded 20 mg / 100 g, indicating that the shrimp was no longer fresh. On the third day, the colors of the PSP, PSP / PET-120, PSP / PET-140 and PSP / PET-160 films all turned blue, showing a good effect of indicating the freshness of the shrimp. The above results show that the PSP / PET-120, PSP / PET-140 and PSP / PET-160 films have excellent ability to indicate the freshness of shrimp in a high humidity environment.

Claims

1. A composite food freshness indicator film, characterized in that: The invention comprises an anthocyanin food freshness indicator film and a commercial pre-coated film. The anthocyanin food freshness indicator film is thermally laminated with the commercial pre-coated film through a thermal laminating technology to obtain a composite film.

2. The composite food freshness indicator film according to claim 1, characterized in that: The anthocyanin food freshness indicator film is a purple sweet potato film.

3. The composite food freshness indicator film according to claim 1, characterized in that: The commercial pre-coated film is a PET film or a BOPP film.

4. A method for preparing the composite food freshness indicator film according to any one of claims 1 to 3, characterized in that: The following steps are involved: The anthocyanin food freshness indicator film is subjected to a heat laminating process on a heat laminating machine equipped with a commercial pre-coated film to obtain a composite film; The anthocyanin food freshness indicator film is a purple sweet potato film, and the preparation method comprises the following steps: (1) The purple sweet potato is sterilized by high pressure steam and then homogenized to obtain purple sweet potato juice; (2) adding a plasticizer to the purple sweet potato juice obtained in step (1) to obtain a mixed solution of purple sweet potato juice and the plasticizer; (3) pouring the mixed solution of purple sweet potato juice and plasticizer obtained in step (2) into a mold and drying it to obtain a purple sweet potato film.

5. The method for preparing a food freshness indicator film according to claim 4, characterized in that: When the pre-coating film is a PET pre-coating film, the heat mounting treatment temperature is 110-160°C.

6. The method for preparing the food freshness indicator film according to claim 4, characterized in that: When the pre-coated film is a BOPP pre-coated film, the heat lamination treatment temperature is 80-130°C.

7. The method for preparing a food freshness indicator film according to claim 4, characterized in that: The speed of the heat mounting process is 0.5-2 m / min.

8. The method for preparing a food freshness indicator film according to claim 4, characterized in that: In step (1), the high-pressure steam sterilization treatment is to put the purple sweet potato into a sterilizing pot and maintain it at 115-121° C. for 30-40 minutes under 103.4 kPa.

9. The method for preparing a food freshness indicator film according to claim 4, characterized in that: In step (2), the plasticizer is polyethylene glycol, and the added amount of polyethylene glycol is 10% to 30% of the weight of the purple sweet potato.

10. The method for preparing a food freshness indicator film according to claim 4, characterized in that: The homogenization is as follows: adding the purple sweet potato sterilized by high-pressure steam into hot water for homogenization treatment, wherein the temperature of the hot water is 80-100° C., and the material-liquid ratio of the purple sweet potato to the hot water is 1:15-1:25 g / mL.

Citation Information

Patent Citations

  • Digital pre-laminating film

    CN101705060A

  • Method for preparing freshness indicating film based on purple sweet potato powder subjected to different heat treatments

    CN115558140A